If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5xt + -3xy = 0 Solving 5tx + -3xy = 0 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '3xy' to each side of the equation. 5tx + -3xy + 3xy = 0 + 3xy Combine like terms: -3xy + 3xy = 0 5tx + 0 = 0 + 3xy 5tx = 0 + 3xy Remove the zero: 5tx = 3xy Divide each side by '5x'. t = 0.6y Simplifying t = 0.6y
| h(-0.5)=-4.5+3 | | y+.6=.8(y+2) | | y+.6=.8(y+2) | | Y=2b^2+4+9b | | [4x]=18+7y | | 2.3w+7+8.1+3w= | | 4.25*16= | | 10(2-m)-5(1-3m)=30 | | 0.53+0.34t=3.44t-0.71 | | 4y+16x=32 | | 0.53+0.34t=3.44t-0.71 | | 10(2-m)-5(1-3m)=30 | | 30+4n=95 | | 114=-6(2x-7) | | [7x-10]=X-6 | | 1.25+3y=7.25 | | -8(4m-6)=16(2m-5) | | 7x+3(4x-12)=154 | | -1(x+5)=3(x+9)-10 | | x+3(2x+4)=47 | | 3(2m-1)+m=m-3 | | 46+4x=-6x | | 8+3y=-7 | | findvc=kpv | | [5x+8]=x+12 | | 4(3m-5)-m=-m+16 | | (25)+(x+15)=(3x-10) | | Y=-0.414(70)+106.55 | | -1(x+m)=3(x+9)-10 | | 3x+-4=x+2 | | -85=5(1-3x) | | 18-(3-2m)=3(m-5) |